Neutralizing disputes raised by The USA on protection of pharmaceutical inventions during TPP negotiations - Hai, Tran Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This paper deals with disputes on protection of pharmaceutical inventions between the nations participating in the negotiations of Trans-Pacific Strategic Economic Partnership Agreement (referred afterwards as TPP). The case study is related to a traditional receipt of which would show clearly the differences in legal regulations of protection of inventions among certain nations. At the same time, the paper presents the studies of proposals made by the US during the TPP negotiations in connection to pharmaceutical inventions. The paper proposes a consensus solution for the raised disputes on basis of studies made for TRIPS Agreement, comparison of UD proposals with the stipulations of human rights, Doha Declaration on TRIPS Agreement and Health of Communities 2001 and the International Convention 1966 on Economic, Social and Cultural Rights.